Socrates on virtue and selfknowledge in Alcibiades I and Aeschines' Alcibiades - Pentassuglio, Francesca (Revista Archai, 2014)
The paper focuses on the concepts of virtue and self-knowledge in Alcibiades I and Aeschines’ Alcibiades, which are marked by striking similarities in the way they discuss these themes and their interconnection. First of all, in both dialogues the notions of á¼€Î¼Î±Î¸Î¯Î± and á¼€ÏÎµÏ„á½µ seem to be connected and both are bound up with the issue of Îµá½Î´Î±Î¹Î¼Î¿Î½Î¯Î±: Socrates points out that á¼€ÏÎµÏ„á½µ is the only source of true Îµá½Î´Î±Î¹Î¼Î¿Î½Î¯Î± and encourages Alcibiades to acquire it, stressing the need for a constant á¼Ï€Î¹Î¼á½³Î»ÎµÎ¹Î± á¼‘Î±Ï…Ï„Î¿á¿¦. Thus, another common feature is the Socratic exhortation to pursue and achieve moral virtue, which is identified as a form of knowledge. Ultimately, in both accounts the chief means by which to contrast á¼€Î¼Î±Î¸Î¯Î± is found in the care and knowledge of the self. The above arguments are to be considered within the particular frame of the paideutic relationship between Socrates and Alcibiades, which is itself portrayed in similar terms in the two texts. In both dialogues, the relationship is characterized as a form of erotic education and, moreover, Socrates himself links his paideutic activity to divine will. Yet, only in Aeschines’ Alcibiades does this explicitly entail the idea that Socrates transmits virtue without resorting to any Ï„á½³Ï‡Î½Î· or á¼Ï€Î¹ÏƒÏ„á½µÎ¼Î·. So while in both cases á¼€ÏÎµÏ„á½µ is understood as a kind of knowledge, in Aeschines’ Alcibiades there seems to be a greater tension between this concept of virtue and its modes of transmission, which are “anepistemic”.